High Random Blood Glucose Level before Surgery as a Risk Factor for Recurrent Event in Epithelial Ovarian Carcinoma : Kadar Gula Darah Sewaktu yang Tinggi sebelum Operasi sebagai Faktor Risiko Kejadian Residif pada Pasien Karsinoma Ovarium Tipe Epitelial - Anggiyasti V. Hapsari; Teuku M. Iskandar (Indonesian Socety of Obstetrics and Gynecology, 2022)
Abstract Objective : To investigate the high random blood glucose level as a risk factor for recurrent disease in EOC patient at Kariadi General Hospital. Methods: Sixty six patients diagnosed as EOC in Kariadi General Hospital were divided into 2 groups: 30 patients with recurrent disease and 30 patients without recurrent disease after completing chemotherapy cycles. We analysed correlation between age of diagnosis, tumour mass location, Ca-125 level, histological subtype and random blood glucose level before surgery with recurrent disease. Result: There is no significantly difference in age of diagnosis, tumour mass location and histological subtypes between two groups. However, recurrent EOC patients have higher Ca-125 level significantly than non-recurrent patients (327.8±250.5 vs 183.5±212.1 respectively; p = 0,01). Mean of random blood glucose level of recurrent patients is also higher than non-recurrent patients significantly (150.5 ±79 vs 110.8 ± 31.1 respectively; p = 0.006). Patient with random blood glucose level > 110 mg/dl have 3 times more likely to develop recurrence in EOC patient significantly with 95% CI. Conclusion: The mean of random blood glucose level in recurrent EOC patients is significantly higher than non-recurrent EOC patients. Patient with random blood glucose level > 110 mg/dl have 3 times more likely to develop recurrence in EOC patient. Keyword: epithelial ovarian cancer, random blood glucose level, recurrent. Abstrak Tujuan: Untuk membuktikan kadar glukosa darah sewaktu yang tinggi sebagai faktor risiko kejadian residif pada pasien karsinoma ovarium epitelial di RSUP dr. Kariadi. Metode: Enam puluh pasien yang telah didiagnosis sebagai karsinoma ovarium epitelial di RSUP dr. Kariadi dibagi menjadi 2 kelompok: 30 pasien pada kelompok residif dan 30 pasien pada kelompok non-residif berdasarkan evaluasi setelah menyelesaikan siklus kemoterapi. Data yang dianalisis meliputi usia saat terdiagnosis, lokasi tumor, kadar Ca-125, subtipe histologi, kadar gula darah sewaktu (GDS) sebelum operasi dan hubungannya dengan kejadian residif. Hasil: Tidak terdapat perbedaan yang bermakna dalam usia saat diagnosis, lokasi tumor dan subtipe histologis diantara kedua kelompok. Namun, kelompok pasien residif memiliki kadar Ca-125 yang lebih tinggi secara bermakna dibandingkan kelompok pasien non-residif (327,8 ± 250,5 vs 183,5 ± 212,1; p = 0,01). Rerata kadar GDS pada kelompok pasien residif juga lebih tinggi secara bermakna daripada kelompok non-residif (150,5 ± 79 vs 110,8 ± 31,1; p = 0,006). Pasien dengan kadar GDS > 110 mg/dl memiliki risiko 3 kali lipat untuk menjadi residif secara bermakna dengan tingkat kepercayaan 95%. Kesimpulan: Rerata kadar GDS pada kelompok pasien residif lebih tinggi secara bermakna dibanding kelompok pasien non-residif. Pasien dengan kadar GDS > 110 mg/dl memiliki risiko 3 kali lipat untuk menjadi residif Kata kunci: kadar gula darah sewaktu, karsinoma ovarium epitelial, residif.